Horticultural reviews :Volume 43 - Janick, Jules, 1931- (Hoboken, New Jersey : Wiley-Blackwell, 2015)
Horticultural Reviews presents state-of-the-art reviews on topics in horticultural science and technology covering both basic and applied research. Topics covered include the horticulture of fruits, vegetables, nut crops, and ornamentals. These review articles, written by world authorities, bridge the gap between the specialized researcher and the broader community of horticultural scientists and teachers.
Includes bibliographical references and indexes.
Online resource; title from PDF title page (Wiley, viewed July 20, 2016).
Keywords: Horticulture; Horticulture -- Research; Horticulture; Horticulture -- Research; SCIENCE / Life Sciences / Botany; Electronic books